Implementasi Virtual Reality dalam Visualisasi Arsitektur Kampus Menggunakan Game Development Life Cycle (GDLC) - Hidayat, Muhammad Hafid; Maulana, Oka Wahyu; Oktavianto, Hardian; Muharom, Lutfi Ali; Cahyanto, Triawan Adi; Saifudin, Ilham (Puslitbang Sinergis Asa Professional, 2025)
Campus promotions often still rely on conventional media such as brochures, mockups, or 2D videos which are less attractive to the digital generation. This presents a challenge in effectively conveying the university's image and excellence to prospective students, especially high school students. To overcome these problems, this research aims to develop a campus architectural visualization system based on Virtual Reality (VR) technology as a promotional media for Muhammadiyah University. This system was developed using the Game Development Life Cycle (GDLC) method, which includes initiation, pre-production, production, testing, and post-production stages. 3D models of the campus buildings were created using Blender and integrated into Unity to build an interactive VR environment. Key features include virtual campus navigation, detailed 3D visualizations, and interactive information presentation. Testing was conducted using the black-box method and usability evaluation. The results show that the VR application is able to provide an interesting and informative campus exploration experience. This system is expected to be an effective and modern promotional media, and is able to increase prospective students' interest in the campus.